Interfacial Microstructure Characteristics and Mechanical Properties of a Press Bonded Ti–5Al–2Sn–2Zr–4Mo–4Cr Alloy - Hong Li (MDPI AG, 2021)
The microstructure evolution characteristics and the shear strength of bond and base alloys were investigated during the press bonding of the Ti–5Al–2Sn–2Zr–4Mo–4Cr alloy. The quantitative detection of the interfacial void shows that the interfacial voids shrunk gradually with time and a bond free of voids could be obtained at the time above 10 min. The microstructure of the base alloy shows that the primary α phase tends to be equiaxed because of the increase in plastic deformation and the variation in the volume fraction and grain size of the primary α phase that are complicated with time. The grain boundary misorientation characteristics in bond and base alloys are not consistent. However, they tend to be comparable over time. The shear strength of bond and base alloys at different times was explained and compared. The compared results indicate that the enhanced strength of the bond is mainly due to the increase in the bonded area. However, the strength of the bond decreases slightly because of the slight coarsening of the grain size and the decrease in the volume fraction of the primary α phase at the time more than 20 min. The shear strength of the bond and base alloys tends to be highest and close at 10 min.